A comparative study on the prevalence of periodontal disease in a selected urban and rural area - Rosanes, Rose Anne Q.; Santos, Rachel Ann P.; Vergel de Dios, Nanette (Adviser).
The aim of this study is to compare the prevalence of periodontal disease in a selected urban and rural area. A total of 134 subjects were examined, 68 from an urban area (Moonwalk Village in Las Pinas) and 66 from a rural area (Alfonso, Cavite). Simplified Oral Hygiene Index and CPITN scores were takne and the subjects' socioeconomic status was recorded. Statistical analysis of the results were done using the z-test of two proportions. Results show that the most prevalent periodontal disease by severity is gingivitis or stable lesion at 54.41% and 63.64% for the urban and rural area, respectively. The progressive lesion was higher in the urban area at 30.88% than the rural area at 27.27%. Healthy periodontium occured at 14.71% and 9.09% for the urban and rural areas, respectively. Statistical analysis of the results show that there is no significant difference in the prevalence of periodontal disease between the urban and rural area examined. This result an be attributed to the finding that there is no statistically significant correlation between the prevalence of periodontal disease, oral hygiene and socioeconomic status, i.e educational attainment and annual family income, which are the commonly conceived factors leading to differences int he prevalence of the disease between these areas. Treatment need for both areas is TN2 which is improved oral hygiene and scaling.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Periodontal diseases